Bacterial back-talk: structural stability, unfolding and molecular interaction studies on Staphylococcal proteins - Zandomeneghi, Sara (2023)
The structural characterisation of proteins is key to understanding their biological functions and interactions. Many different biophysical techniques have been developed in the last century to achieve protein structure determination, among which crystallography has become the most common and successful. The physical constraints imposed by crystallography, though, such as low temperatures and the tight packing of molecules, cause the loss of important biological information especially when it comes to soluble proteins. In a native environment, these move freely in an aqueous environment and can display varying degrees of flexibility to accommodate for molecular interactions. The structure obtained by crystallizing the protein might therefore not be truly representative of the conformation adopted under physiological conditions. Different biophysical techniques, such as circular dichroism and small angle X-ray and neutron scattering were combined with computational tools to characterise the structure and molecular interactions of proteins in a way that allows to retain physiological conditions. This methodology was developed and applied to the proteins of the quorum-sensing system (or accessory gene regulator, agr) in Staphylococcus aureus, a Gram-positive pathogen which is often responsible for post-operative infections in hospital patients. The agr system is responsible for the collective behaviour and control of infection phases in S. aureus and an understanding of the mechanism of action of these not yet fully characterised proteins will inform on potential pathway inhibitors to improve patient prognosis without encouraging antibiotic resistance. Particular focus was on the agr two-component system. Two-component systems are a signal transduction mechanism comprising of a membrane receptor and a response regulator widely found in bacteria. Specifically, molecular dynamics simulations were used to create atomic-level models, small angle scattering to investigate oligomeric state, create low-resolution models and identify single or multiple conformations and CD and SAXS to identify molecular interactions. The cytoplasmic domains of AgrC, the histidine kinase in the two-component system of the agr system, were shown to retain a dimeric state even in absence of the transmembrane region, and an MD-generated model was validated by SAXS. An experimentally validated model of full-length AgrA, the response regulator, was also identified. The effect of ATP, which acts as phosphor-donor, was investigated by both CD and SAXS. A non-hydrolysable analogue, sATP, was found to alter the compactness of AgrC206 (the cytoplasmic domain of AgrC) and affect its thermal response. SANS studies supplied information on the behaviour of AgrC206 and AgrA while in a complex. The effect of ATP on AgrA was shown to be dependent on the interaction between the two proteins.